DINAMIKA ISLAMISASI MAKKAH & MADINAH - Mohammad Arif (Asketik : Jurnal Agama dan Perubahan Sosial, 2018)
The development of Islam during the time of Prophet Muhammad, through various kinds of trials and challenges faced to spread it. At the beginning of Prophet Muhammad SAW. got a revelation from Allah SWT. which called for humans to worship him, received great challenges from various circles of Quraysh. This happened because at that time the Quraysh had another offering of idols made by themselves. Because of such circumstances, the first da'wah performed in Mecca was conducted in secret, especially since the number of people who converted to Islam was very small. Quantity of people who embraced Islam more and more in days, God also ruled the Prophet to do da'wah openly. Increasingly new believers brought by Prophet Muhammad SAW. Allah SWT. ordered the Prophet Muhammad along with other Muslims to emigrate to the city of Medina. This is where a new chapter of Islamic progress begins. Islamic propagation done by the Prophet either secretly or openly, received various responses (responses). Although it can be said that Arab society in the city of Makkah there is a sincere acceptance of Islamic teachings, but in general the Arab community of Makkah city refused and did not want the presence of Islam and Muslims and Muslims in the city. After several years of individual accusation the orders were taken for the Prophet to openly indict and the next step was to accuse the general. The Prophet began calling the whole society to Islam openly. After the accusation of the light, the Quraish leader began to try to obstruct the Apostle's doom. The increasing number of the Prophet's increasingly stronger the challenges of the Quraisy. According to Ahmad Shalabi, there are five factors that encourage quraisy people to oppose the call of Islam: 1) They cannot distinguish between prophethood and power. 2) Prophet Muhammad called on the noble right with hambah sahaya. 3) The Quraysh cannot accept the teachings of the resurrection and the vengeance of the Hereafter. 4) Taklid to the ancestors is a deeply entrenched habit in the Arab nation. 5) Sculptors and sculptors view Islam as a barrier of sustenance. There are many ways that the leaders of quraisy to prevent propaganda from the diplomatic way Muhammad accompanied by persuasion until the violence was launched to stop the propagation of the Prophet. But the Prophet Muhammad remained in the position to broadcast the religion of Islam.